Diminishing Connectivity Failures by Auto-Reconfiguration in WSN - K. Gugan; V. Saravanan (Institute of Advanced Engineering and Science, 2017)
The Wireless Sensor Network is one of the most significant purposes behind the accomplishment of long range wireless communication. Frequent connectivity failures are occurred in the sensor-organised network due to obstruction, snags, message drop because of node energy depletion; obstacle and so forth. The total communication gets collapsed if there any lessening in the nature of correspondence or quality between the sensor nodes or from the sensor nodes to the sink nodes and this prompts to connection failures. To overcome the frequent connectivity failures we propose Diminishing Connectivity Failures by Auto-Reconfiguration in WSN (DCFA). This scheme provides steadfast routes to reduce the connectivity failure and improve the network performance.